1998
DOI: 10.1161/01.atv.18.2.323
|View full text |Cite
|
Sign up to set email alerts
|

von Willebrand Factor Does Not Influence Atherogenesis in Arteries Subjected to Altered Shear Stress

Abstract: Abstract-The role of von Willebrand factor (vWF) in arterial neointimal formation that develops in arteries with altered shear stress was investigated using normal, heterozygous, and homozygous von Willebrand disease pigs (ie, vWD, or lacking vWF) that were fed normal pig chow. Shear stress was applied to carotid and femoral arteries with a Goldblatt clamp for 14 days, producing a Ն80% stenosis. Neointimal lesion size was measured by computer-assisted morphometry. Expression of proliferative cell nuclear antig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

1999
1999
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 57 publications
(43 reference statements)
0
12
0
Order By: Relevance
“…On the other hand, a study of von Willebrand disease in pigs has indicated that vWF was not essential for neointimal development in normal carotid and femoral arteries. 45 In this study, a bolus injection of monoclonal antibody against vWF reduced not only thrombus formation but also subsequent neointimal SMC proliferation and neointimal development after the second balloon injury. Our result supports an important role for vWF in neointimal growth.…”
Section: Discussionmentioning
confidence: 56%
“…On the other hand, a study of von Willebrand disease in pigs has indicated that vWF was not essential for neointimal development in normal carotid and femoral arteries. 45 In this study, a bolus injection of monoclonal antibody against vWF reduced not only thrombus formation but also subsequent neointimal SMC proliferation and neointimal development after the second balloon injury. Our result supports an important role for vWF in neointimal growth.…”
Section: Discussionmentioning
confidence: 56%
“…Furthermore, homozygote vWF deficient pigs show a resistance to the initiation and progression of spontaneous and diet-induced atherosclerosis, 41 but vWF appeared not essential for shear-induced smooth muscle cell accumulation in the intima. 7 Therefore, the vWF deposits seem not to be important for this early step in the development of atherosclerosis. However, deposition of vWF could play a role in a later step of atherogenesis.…”
Section: De Meyer Et Al Intimal Deposition Of Von Willebrand Factormentioning
confidence: 97%
“…6 Accumulation of vWF in intimal thickening may be the result of increased synthesis and release by ECs, an influx from the plasma and/or platelets, or a decreased rate of removal of vWF from the extracellular matrix. 7 The aim of the present study was to investigate whether the intimal deposition of vWF is due to an increased synthesis of the protein and whether subendothelial deposition of vWF also occurs after cholesterol-induced plaque formation and whether this has functional consequences for platelet adhesion.…”
mentioning
confidence: 99%
“…Finally, vWf plays an important role not only in platelet adhesion and aggregation but also in coagulation 42,43 and may thus enhance the risk of thrombogenesis. Accordingly, the increase of vWf within 48 hours after a myocardial infarction was a predictor of the rate of restenotic cardiovascular events within 14 days, whereas the increase of CRP, as a marker of acute-phase response, was not.…”
Section: Jager Et Al Vwf and Crp As Predictors Of Mortality 3075mentioning
confidence: 99%